CITED2 Mediates Metabolic Reprogramming in Renal Tubular Epithelial Cells via the AKT Signaling Pathway to Induce Sepsis-Associated Acute Kidney Injury - Deng R; Yang H; Zhong W; Zhou J; Huang G; Zeng K (Journal of Inflammation Research)
Ruiming Deng,1,2,* Hang Yang,1,* Weibo Zhong,2 Juan Zhou,3 Guiming Huang,2 Kai Zeng1 1Department of Anesthesiology, The First Affiliated Hospital of Fujian Medical University, Fuzhou City, Fujian Province, 350004, People’s Republic of China; 2Department of Anesthesiology, Ganzhou People’s Hospital, Ganzhou City, Jiangxi Province, 341000, People’s Republic of China; 3Department of Thyroid and Breast Surgery, Ganzhou People’s Hospital, Ganzhou City, Jiangxi Province, 341000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kai Zeng, Department of Anesthesiology, The First Affiliated Hospital of Fujian Medical University, Fuzhou City, Fujian Province, 350004, People’s Republic of China, Email fymzk6822@163.com Guiming Huang, Department of Anesthesiology, Ganzhou People’s Hospital, Ganzhou City, Jiangxi Province, 341000, People’s Republic of China, Email huangguiming@mail.gzsrmyy.comBackground: Sepsis-associated acute kidney injury (S-AKI) is a prevalent and severe clinical complication in intensive care units (ICUs) and is associated with high mortality and poor prognosis. The dysfunction of renal tubular epithelial cells (TECs), particularly through their metabolic reprogramming, plays a critical role in the onset and progression of S-AKI. CITED2 is shown to regulate a variety of cellular processes, but its specific impact on TECs metabolism and S-AKI pathogenesis remains unclear. The aim of this study was to investigate the role of CITED2 in the metabolic reprogramming of TECs and its effects on inflammation and kidney injury in S-AKI.Material and Methods: The C57BL/6 mouse model of S-AKI was established using cecal ligation and puncture (CLP). We assessed the inflammatory responses, glucose metabolism and CITED2 expression in the kidneys of septic mice. Additionally, the effect of CITED2 on TECs metabolism and inflammation was evaluated using in vivo and in vitro models. CITED2 silencing and overexpression were employed to elucidate its regulatory role, focusing on the AKT signaling pathway.Results: S-AKI causes structural and functional kidney damage, aggravated inflammatory responses, and dysregulated glucose metabolism, accompanied by increased expression of CITED2. CITED2 silencing attenuated TECs metabolic dysfunction and reduced inflammation, thereby protecting the kidney from injury. Conversely, CITED2 overexpression exacerbated TECs metabolic dysfunction, promoted inflammatory responses, and worsened kidney injury. Mechanistically, CITED2 regulates TEC metabolism through the AKT signaling pathway, promoting S-AKI-related inflammation and contributing to kidney injury.Conclusion: CITED2 drives the metabolic reprogramming of TECs through the AKT signaling pathway, thereby aggravating the inflammatory response and leading to kidney injury, highlighting its critical role in S-AKI. Targeting CITED2 inhibition may represent a novel therapeutic approach for managing S-AKI.Keywords: CITED2, Sepsis, Acute kidney injury, Metabolic reprogramming, TECs